The complete chloroplast genome sequence of a medicinal orchid species Coelogyne fimbriata (Orchidaceae). Issue 3 (2nd July 2020) - Yue, Ziyang; Kao, Huixia; Zhang, Yu; Wang, Tiemei; Dong, Shubin; Cheng, Jin
Abstract: Coelogyne fimbriata is an important orchid species with high medicinal value. Its complete chloroplast genome is 158, 935 bp in length, which possesses the typical structure consising of a small single-copy region (SSC) of 18, 743 bp, two inverted repeats (IRs) of 26, 374 bp, and a large-single copy region (LSC) of 87, 444 bp. The genome encodes 137 genes, including 91 protein-coding genes (PCGs), 38 tRNA genes and 8 rRNA genes. And the overall GC content is 37.40%. In addition, our phylogenetic analysis based on cp genome revealed the phylogenetic relationship between C. fimbriata and other 22 species in Orchidaceae.